2003
DOI: 10.1186/1472-6882-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine (CAM) use by african american (AA) and caucasian american (CA) older adults in a rural setting: a descriptive, comparative study

Abstract: BackgroundThe use of CAM is at an all time high. There is very little research that compares the use of CAM in elders by ethnicity in rural settings. The purpose of the study was to determine if there was a difference between African American and Caucasian American rural elders on use of CAM and self-reported satisfaction with CAM.MethodsThe design was a descriptive, comparative study of 183 elders who reported the number of CAM used and satisfaction with CAM. A convenience sample was recruited through communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
2
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 10 publications
4
41
2
6
Order By: Relevance
“…2-7,9,15,16,26-29 Some researchers have attributed this difference to the perception of discrepancies of health care treatment by blacks, lower average educational levels of blacks compared to whites, and the lack of accessibility to DC s in black communities. 2,4,20,21,30 In this study, researchers found that non-Hispanic black patients that do use chiropractic services have a positive outlook on doctor-patient interactions with their DC, they often are college graduates, and they live within 30 minutes of their DC. In addition, researchers found that non-Hispanic black women marginally use chiropractic services more often than men, which is in congruence with existing CAM research overall.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…2-7,9,15,16,26-29 Some researchers have attributed this difference to the perception of discrepancies of health care treatment by blacks, lower average educational levels of blacks compared to whites, and the lack of accessibility to DC s in black communities. 2,4,20,21,30 In this study, researchers found that non-Hispanic black patients that do use chiropractic services have a positive outlook on doctor-patient interactions with their DC, they often are college graduates, and they live within 30 minutes of their DC. In addition, researchers found that non-Hispanic black women marginally use chiropractic services more often than men, which is in congruence with existing CAM research overall.…”
Section: Discussionmentioning
confidence: 87%
“…[2][3][4][5][6][7][8][9] In one study, for example, Barnes et al 10 demonstrated that 43.1% of white adults sought out CAM treatments in comparison to 25.5% of blacks. Furthermore, there is minimal research that provides an explanation as to why blacks use CAM less often.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in the United States, use of According to Cuellar, Aycock, Cahill, and Ford (2003), cultural diversity and the health care practices of specific cultures can shape the system of health care in a country. They assert that the assumption that conventional medical practice is the choice for all cultures is incorrect and the inclusion of indigenous healing practices or folk remedies is often ignored or not discussed.…”
Section: Current Researchmentioning
confidence: 99%